Structure of human GPR119-Gs complex binding APD597 and characterization of GPR119 binding agonists - Li, Ruixue; Qian, Yuxia; Wang, Jiening; Han, Zhen; Ye, Sheng; Wu, Shan; Qiao, Anna (Frontiers in Pharmacology, 2024)
The rhodopsin-like receptor GPR119 plays a crucial role in glucose homeostasis and is an emerging target for the treatment of type 2 diabetes mellitus. In this study, we analyzed the structure of GPR119 with the agonist APD597 bound and in complex with the downstream G protein trimer by single particle cryo-electron microscopy (cryo-EM). Structural comparison in combination with function assay revealed the conservative and specific effects of different kinds of GPR119 agonists. The activation mechanism of GPR119 was analyzed by comparing the conformational changes between the inactive and active states. The interaction between APD597 derivatives and synthetic agonists with GPR119 was analyzed by molecular docking technique, and the necessary structural framework was obtained. The above conclusions can provide structural and theoretical basis for the development of therapeutic drugs for type 2 diabetes mellitus.